In Defence of Virtue: The Legitimacy of Agent-Based Argument Appraisal - Andrew Aberdein (Informal Logic, 2014)
Several authors have recently begun to apply virtue theory to argumentation. Critics of this programme have suggested that no such theory can avoid committing an ad hominem fallacy. This criticism is shown to trade unsuccessfully on an ambiguity in the definition of ad hominem. The ambiguity is resolved and a virtue-theoretic account of ad hominem reasoning is defended.